High-Performance Ternary Organic Solar Cells Enabled by Combining Fullerene and Nonfullerene Electron Acceptors - Zhang, Jianyun; Liu, Wenrui; Xu, Shengjie; Zhu, Xiaozhang (Organic Materials, 2019)
Recently, by elaborately designing nonfullerene acceptors and selecting suitable polymer donors great progresses have been made towards binary organic solar cells (OSCs) with power conversion efficiencies (PCEs) over 15%. Ternary organic photovoltaics by introducing a third component into the host binary system is recognized to be highly effective to elevate the performance through extending the light absorption, manipulating the recombination behavior of the carriers, and improving the morphology of the active layer. In this work, we synthesized a new electron-acceptor ZITI-4F matching it with the wide-bandgap polymer donor PBDB-T The PBDB-T:ZITI-4F-based OSC showed a high PCE of 12.33%. After introducing 40% of PC71BM as the third component, the ternary device achieved an improved PCE of 13.40% with simultaneously improved photovoltaic parameters. The higher performance of the ternary device can be attributed to the improved and more balanced charge mobility, reduced bimolecular recombination, and more favorable morphology. These results indicate that the cooperation of a fullerene-based acceptor and a nonfullerene acceptor to fabricate ternary OSCs is an effective approach to optimizing morphology and therefore to increase the performance of OSCs.
Keywords: ternary organic solar cells; electron acceptors; indenoindene; power conversion efficiencies